Advances in alternating current electroluminescent devices - Wang, Lin (2020)
Alternating current (AC)‐driven electroluminescent (EL) devices have recently attracted attention as potential alternatives to direct current (DC)‐driven organic light‐emitting diodes (OLEDs), as they have the great advantage of easy integration into the AC power system of 110/220 V at 50/60 Hz without complicated back‐end electronics. However, the high driving voltage and low power efficiency inherent to AC‐driven EL devices limit their widespread application. While researchers have made some remarkable progress in this field, the underlying causes during the development process remain to be explored. The strategies for improving the performance of AC‐driven EL devices with different configurations, such as the conventional sandwiched structure and multilayer‐based light‐emitting devices, are summarized in this review. For example, it is crucial to enhance the effective electric field around the emitters for AC‐driven thin film electroluminescent (AC‐TFEL) devices, while the unbalanced generation/injection of charge carriers is the main limiting factor for the performance of AC‐driven light‐emitting devices (AC‐LEDs). The recent advances in AC‐driven EL devices, with some new configurations or new‐type emitting materials, are presented by category. The challenges and opportunities for the further development of AC‐driven EL devices are also discussed.